GEOMORPHOLOGICAL ASPECT ANALYSIS IN CIKANGKUNG AND SURROUNDING AREA, CIRACAP SUBDISTRICT, SUKABUMI REGENCY, WEST JAVA - Maulana, Muhammad Hafidz; Pratiwi, Santi Dwi; Rosana, Mega Fatimah (Faculty of Geological Engineering, Universitas Padjadjaran, 2025)
The Ciletuh–Jampang area, located in the southern part of Java Island exhibits distinct geomorphological characteristics shaped by a combination of endogenous and exogenous geological processes over an extended period. This study analyzes the geomorphology of the region using field observations and remote sensing, focusing on morphographic, morphometric, and morphogenetic aspects, specifically in Cikangkung area, Ciracap Subdistrict, Sukabumi Regency, West Java. Based on those three geomorphological aspects, this area could be divided into four different units, such as marine lowland, denudational lowland, gently sloping structural lowhills, and sloping structural lowhills. These units are formed by interactions between tectonic activity, volcanism, weathering, erosion, and sedimentation processes. Tectonic uplift, volcanic contributions, and variations in rock resistance have significantly influenced landforms, while exogenous processes have shaped terrain forms, drainage patterns, and top-soil thickness. The results reveal that these processes not only define the region's unique morphological features but also influence its diverse land use practices, including agriculture and settlements. Keyword: Geomorphology, Ciletuh-Jampang, Cikangkung, Landform, Remote Sensing